Personal wealth from a global perspective - Davies, James B., 1951-; World Institute for Development Economics Research (Oxford : Oxford University Press, 2008)
This volume looks beyond the distribution of income by examining the assets, debts, and net worth of individuals and households to create a global picture of wealth, its distribution and concentration.
"A study prepared for the World Institute for Development Economics Research of the United Nations University (UNU-WIDER)."
Includes bibliographical references and index.
Description based on print version record.
Keywords: Wealth; Economic development; Income distribution